Cervical Cancer Awareness and Its Association with VIA (Visual Inspection with Acetic Acid) Screening Behaviors Among Women of Reproductive Age: A Cross-Sectional Study at Simpang Limun Primary Health Center - Elbert Elbert; Rina Amelia; Felix Khosasi; Anastasia Grace Milenia Ginting; Halisa Tiara Ariani Matondang; Riska Primayanti Batubara (SCRIPTA SCORE Scientific Medical Journal, 2026)
Background: Cervical cancer is a malignant disease that affects the cervix and ranks as the fourth most common cause of cancer globally, according to the World Health Organization. Women over the age of 15 are at high risk, with the most affected age group being 25–64 years. Early detection through screening, such as viasual examintation tests, plays a crucial role in reducing cervical cancer morbidity and mortality. Objectives: This study aims to determine the relationship between the knowledge of women of childbearing age about cervical cancer and VIA tests, and their behavior (attitudes and actions) regarding VIA examination as a screening method for cervical cancer. Methods: This analytical descriptive study used a cross-sectional design. Data were collected through questionnaires distributed to women of childbearing age who visited the Simpang Limun Primary Health Center. The study population included women of childbearing age in the health center's working area. A total of 100 participants were selected using the one-population hypothesis sampling formula. Data were analyzed using the Chi-square test in SPSS. Results: The findings indicate a significant relationship between knowledge about cervical cancer and VIA tests and the behavior (attitudes and actions) of women of childbearing age towards undergoing VIA examinations. Conclusion: Enhancing knowledge about cervical cancer and  tests can positively influence the behavior of women of childbearing age, leading to increased participation in cervical cancer screening. Keyword: Cervical cancer, Screening, VIA test, Knowledge, Behavior Latar Belakang: Kanker serviks merupakan penyakit ganas yang menyerang leher rahim dan menempati peringkat keempat sebagai penyebab kanker tersering di dunia menurut World Health Organization. Wanita berusia di atas 15 tahun berisiko tinggi, dengan kelompok usia yang paling banyak terkena adalah 25–64 tahun. Deteksi dini melalui skrining, seperti pemeriksaan IVA, berperan penting dalam menurunkan angka kesakitan dan kematian akibat kanker serviks. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan wanita usia subur tentang kanker serviks dan tes IVA dengan perilaku (sikap dan tindakan) mereka terhadap pemeriksaan IVA sebagai metode skrining untuk kanker serviks. Metode: Penelitian deskriptif analitik ini menggunakan desain cross-sectional. Data dikumpulkan melalui kuesioner yang dibagikan kepada wanita usia subur yang berkunjung ke Puskesmas Simpang Limun. Populasi penelitian mencakup wanita usia subur di wilayah kerja puskesmas tersebut. Sebanyak 100 partisipan dipilih menggunakan rumus one-population hypothesis sampling formula. Data dianalisis menggunakan uji Chi-square dengan bantuan program SPSS. Hasil: Hasil penelitian menunjukkan adanya hubungan yang signifikan antara pengetahuan tentang kanker serviks dan pemeriksaan IVA dengan perilaku (sikap dan tindakan) wanita usia subur terhadap pemeriksaan IVA. Kesimpulan: Peningkatan pengetahuan tentang kanker serviks dan tes IVA dapat berpengaruh positif terhadap perilaku wanita usia subur, sehingga meningkatkan partisipasi dalam melakukan skrining kanker serviks. Kata Kunci: Cervical cancer, Screening, VIA test, Pengetahuan, Sikap